A general steady-state creep model incorporating dislocation static recovery for pure metallic materials. (October 2022) - Xiao, Xiazi; Li, Shilin; Yu, Long
Highlights: A general steady state creep model is proposed for metallic materials. Dislocation static recovery is taken into account for the evolution of dislocation density. Mechanisms of dislocation climb and thermally activated glide are considered for the dislocation mobility. Calibrated theoretical results can match well with six different sets of experimental data. Abstract: In this work, a mechanistic steady-state creep model is proposed for pure metallic materials to characterize the evolution of macroscopic creep strain rate as a function of the testing temperature and applied stress. Dislocation-dominated and diffusion-dominated creep are both addressed in the developed creep model, which is able to effectively characterize the phenomena of "first-power-law" creep, "five-power-law" creep and "power-law-breakdown" creep. Thereinto, the dislocation-dominated creep behavior is systematically analyzed by considering the evolution of dislocations, which includes dislocation multiplication, strain-rate dependent dynamic recovery and time-related static recovery. Main attentions are focused on the description of dislocation static recovery that covers the annihilation of dislocations induced by the creep mechanisms of dislocation climb and thermally related dislocation glide during the long term plastic deformation. A novel form of the dislocation mobility is deduced that not only considers the effect of dislocation climb and glide, but also takes into account the contribution of mechanical work on atomic diffusion. Moreover, the latter is noticed to be the dominant reason resulting in the transition from "five-power-law" creep to "power-law-breakdown" creep. In order to verify the developed model, creep data of six metallic materials with different crystalline structures is considered to compare with the theoretical results. Good agreement is achieved for all these data over a wide range of temperature and stress, which indicates that the model can well characterize the deformation behavior during the steady-state creep stage. In addition, the contribution of dislocation multiplication, dynamic recovery and static recovery to the evolution of dislocation density is further discussed at different temperatures and stresses, which can facilitate the comprehension of the fundamental creep mechanisms of metallic materials. Graphical abstract: Image, graphical abstract